BDV Syndrome: An Emerging Syndrome with Profound Obesity and Neurodevelopmental Delay Resembling Prader-Willi Syndrome - Bosch, Elisabeth; Hebebrand, Moritz; Popp, Bernt; Penger, Theresa; Behring, Bettina; Cox, Helen; Towner, Shelley; Kraus, Cornelia; Wilson, William G.; Khan, Shagufta; Krumbiegel, Mandy; Ekici, Arif Bülent; et al. (Journal of Clinical Endocrinology and Metabolism, 2021)
Context: CPE encodes carboxypeptidase E, an enzyme that converts proneuropeptides and propeptide hormones to bioactive forms. It is widely expressed in the endocrine and central nervous system. To date, 4 individuals from 2 families with core clinical features including morbid obesity, neurodevelopmental delay, and hypogonadotropic hypogonadism, harboring biallelic loss-of-function (LoF) CPE variants, have been reported. Objective: We describe 4 affected individuals from 3 unrelated consanguineous families, 2 siblings of Syrian, 1 of Egyptian, and 1 of Pakistani descent, all harboring novel homozygous CPE LoF variants. Methods: After excluding Prader-Willi syndrome (PWS), exome sequencing was performed in both Syrian siblings. The variants identified in the other 2 individuals were reported as research variants in a large-scale exome study and in the ClinVar database. Computational modeling of all possible missense alterations allowed assessing CPE tolerance to missense variants. Results: All affected individuals were severely obese with neurodevelopmental delay and other endocrine anomalies. Three individuals from 2 families shared the same CPE homozygous truncating variant c.361Câ€ >â€ T, p.(Arg121∗), while the fourth carried the c.994del, p.(Ser333Alafs∗22) variant. Comparison of clinical features with previously described cases and standardization according to the Human Phenotype Ontology terms indicated a recognizable clinical phenotype, which we termed Blakemore-Durmaz-Vasileiou (BDV) syndrome. Computational analysis indicated high conservation of CPE domains and intolerance to missense changes. Conclusion: Biallelic truncating CPE variants are associated with BDV syndrome, a clinically recognizable monogenic recessive syndrome with childhood-onset obesity, neurodevelopmental delay, hypogonadotropic hypogonadism, and hypothyroidism. BDV syndrome resembles PWS. Our findings suggest missense variants may also be clinically relevant.
CRIS-Team Scopus Importer:2021-12-24
Keywords: BDV syndrome; carboxypeptidase E; CPE; hypogonadotropic hypogonadism; neurodevelopmental disorder; obesity

De novo missense variants in FBXO11 alter its protein expression and subcellular localization - Gregor, Anne; Meerbrei, Tanja; Gerstner, Thorsten; Toutain, Annick; Lynch, Sally Ann; Stals, Karen; Maxton, Caroline; Lemke, Johannes R.; Bernat, John A.; Bombei, Hannah M.; Foulds, Nicola; Hunt, David; et al. (Human Molecular Genetics, 2022)
Recently, others and we identified de novo FBXO11 (F-Box only protein 11) variants as causative for a variable neurodevelopmental disorder (NDD). We now assembled clinical and mutational information on 23 additional individuals. The phenotypic spectrum remains highly variable, with developmental delay and/or intellectual disability as the core feature and behavioral anomalies, hypotonia and various facial dysmorphism as frequent aspects. The mutational spectrum includes intragenic deletions, likely gene disrupting and missense variants distributed across the protein. To further characterize the functional consequences of FBXO11 missense variants, we analyzed their effects on protein expression and localization by overexpression of 17 different mutant constructs in HEK293 and HeLa cells. We found that the majority of missense variants resulted in subcellular mislocalization and/or reduced FBXO11 protein expression levels. For instance, variants located in the nuclear localization signal and the N-terminal F-Box domain lead to altered subcellular localization with exclusion from the nucleus or the formation of cytoplasmic aggregates and to reduced protein levels in western blot. In contrast, variants localized in the C-terminal Zn-finger UBR domain lead to an accumulation in the cytoplasm without alteration of protein levels. Together with the mutational data, our functional results suggest that most missense variants likely lead to a loss of the original FBXO11 function and thereby highlight haploinsufficiency as the most likely disease mechanism for FBXO11-associated NDDs.
CRIS-Team Scopus Importer:2022-03-04

Detection rate and re-analysis of exome sequencing data in a cohort of 207 individuals with neurodevelopmental disorders - Hebebrand, Moritz; Thiel, C. T.; Kraus, Cornelia; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Heterozygous UBR5 variants result in a neurodevelopmental syndrome with developmental delay, autism, and intellectual disability - Sabeh, Pascale; Dumas, Samantha A.; Maios, Claudia; Daghar, Hiba; Korzeniowski, Marek; Rousseau, Justine; Lines, Matthew; Guerin, Andrea; Millichap, John J.; Landsverk, Megan; Grebe, Theresa; Lindstrom, Kristin; et al. (American Journal of Human Genetics, 2025)
E3 ubiquitin ligases have been linked to developmental diseases including autism, Angelman syndrome (UBE3A), and Johanson-Blizzard syndrome (JBS) (UBR1). Here, we report variants in the E3 ligase UBR5 in 29 individuals presenting with a neurodevelopmental syndrome that includes developmental delay, autism, intellectual disability, epilepsy, movement disorders, and/or genital anomalies. Their phenotype is distinct from JBS due to the absence of exocrine pancreatic insufficiency and the presence of autism, epilepsy, and, in some probands, a movement disorder. E3 ubiquitin ligases are responsible for transferring ubiquitin to substrate proteins to regulate a variety of cellular functions, including protein degradation, protein-protein interactions, and protein localization. Knocking out ubr-5 in C. elegans resulted in a lower movement score compared to the wild type, supporting a role for UBR5 in neurodevelopment. Using an in vitro autoubiquitination assay and confocal microscopy for the human protein, we found decreased ubiquitination activity and altered cellular localization in several variants found in our cohort compared to the wild type. In conclusion, we found that variants in UBR5 cause a neurodevelopmental syndrome that can be associated with a movement disorder, reinforcing the role of the UBR protein family in a neurodevelopmental disease that differs from previously described ubiquitin-ligase-related syndromes. We also provide evidence for the pathogenic potential loss of UBR5 function with functional experiments in C. elegans and in vitro ubiquitination assays.
CRIS-Team Scopus Importer:2025-01-31
Keywords: autism; autosomal dominant; developmental disease; epilepsy; intellectual disability; Mendelian phenotype; movement disorders; ubiquitin; UBR5

Identification and characterization of a GLMN splice site variant in a family with glomuvenous malformations - Skowronek, Dariush; Hebebrand, Moritz; Erber, Ramona; Agaimy, Abbas; Zweier, Christiane; Felbor, Ute; Rath, Matthias (European Journal of Dermatology, 2020)
CRIS-Team Scopus Importer:2020-06-26

Identification and characterization of a GLMN splice site variant in a three-generation-family with glomuvenous malformations - Skowronek, D.; Hebebrand, Moritz; Erber, Ramona; Agaimy, Abbas; Zweier, Christiane; Felbor, U.; Rath, M. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22